2009
DOI: 10.1107/s0907444909011329
|View full text |Cite
|
Sign up to set email alerts
|

A charged residue at the subunit interface of PCNA promotes trimer formation by destabilizing alternate subunit interactions

Abstract: Eukaryotic proliferating cell nuclear antigen (PCNA) is an essential replication accessory factor that interacts with a variety of proteins involved in DNA replication and repair. Each monomer of PCNA has an N-terminal domain A and a C-terminal domain B. In the structure of the wild-type PCNA protein, domain A of one monomer interacts with domain B of a neighboring monomer to form a ring-shaped trimer. Glu113 is a conserved residue at the subunit interface in domain A. Two distinct X-ray crystal structures hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
(34 reference statements)
2
23
0
Order By: Relevance
“…As PCNA-C81R and an unrelated trimer interface mutant have trimerization defects (Freudenthal et al, 2009; Lau et al, 2002), we fractionated the mutant PCNA proteins on a size-exclusion column at a concentration of 2.88 μM. Wild-type PCNA had a retention time of 35 minutes, corresponding to a Stokes radius of 49 Å (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…As PCNA-C81R and an unrelated trimer interface mutant have trimerization defects (Freudenthal et al, 2009; Lau et al, 2002), we fractionated the mutant PCNA proteins on a size-exclusion column at a concentration of 2.88 μM. Wild-type PCNA had a retention time of 35 minutes, corresponding to a Stokes radius of 49 Å (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It was, therefore, suggested that the G178S mutation prevented ubiquitylation of Lys-164 in PCNA (41), although this has not been directly tested. In another study, a crystal structure was reported for a PCNA variant carrying one of the two amino acid substitutions present in pol30-113, E113G (42). The structural change in the intermolecular interface region brought about by the E113G substitution was found to be similar to the one in the G178S variant (43).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the absence of Pol stimulation by PCNA-E113G could reflect the fact that this PCNA variant is expected to have a severe defect in the trimer stability under the assay conditions used in that study (a low PCNA concentration and no macromolecular crowding agent; Refs. 42,43). Future studies of PCNA-113 structure could help characterize the changes in the protein that alter its interactions with TLS polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these substitutions (G178S and E113G) are of residues in the β strands that constitute the subunit interface, and the X-ray crystal structures of both mutant proteins reveal perturbations that reduce the number of hydrogen bonds between these strands [90, 91]. The mutant PCNA trimers are less stable than wild-type PCNA, and they are unable to stimulate the catalytic activity of non-classical polymerases [87].…”
Section: The Role Of Pcna In Translesion Synthesismentioning
confidence: 99%